The Effects of Congruence Between Person and Environment on Innovation Performance in Ports - Jiang, Daokui; Liu, Teng; Chen, Zhuo; Zhang, Xiaoyan; Wang, Su; Huang, Tianci; Ning, Lei (Frontiers in Psychology, 2021)
The projected growth and rapid technological development in maritime transportation will create demand for a newly skilled and motivated workforce in the port sector. Thus, it is important for ports to attract, recruit and retain talented employees to promote innovation and enhance competitive advantages. This paper focuses on the welfare and talent of port staff from the perspective of person-environment (P-E) fit. Using polynomial regression with response surface analysis, this study explores the effect of P-E fit on job satisfaction, work engagement and innovation performance, and bootstrapping is applied to confirm the mediating roles of job satisfaction and work engagement in the relationship between P-E fit and innovation performance. Results show that 1) need-supply (N-S) fit and demands-abilities (D-A) fit improved port employees’ job satisfaction, work engagement and innovation performance, and the impacts on work engagement and innovation performance show an inverted "U" and "U" shape, respectively; 2) D-A fit is more important when job satisfaction plays a mediating role; 3) N-S fit makes a greater contribution when work engagement mediates the effect of P-E fit on the innovation performance. These findings contribute to P-E fit research as well as to human resource management practices in ports.